Profiling of naturally occurring proanthocyanidins and other phenolic compounds in a diverse peach germplasm by LC-MS/MS. (1st March 2023) - Zhang, Xianan; Su, Mingshen; Du, Jihong; Zhou, Huijuan; Li, Xiongwei; Zhang, Minghao; Hu, Yang; Ye, Zhengwen
Highlights: 19 PACs and 37 other phenolic compounds were quantified in fruits of 217 peach accessions. Most quantified phenolics showed a vast diversity between tested peach accessions. PACs and other phenolics are affected by peach origins, fruit maturing periods, and fruit types. Peaches with medium astringency had higher levels of PAC and phenolic acid than those without. Abstract: Peach fruits are rich in phenolic compounds and have considerable health benefits. In this study, 19 proanthocyanidins (PACs) and 37 other phenolic compounds are identified and evaluated in the mature fruits of 217 peach accessions using LC-QTRAP-MS/MS and LC-QTOF-MS analyses. Total PAC quantities ranged from 18.93 to 697.52 μg/g fresh weight with a variance of 36.8-fold, and accounted for 11.2 % − 85.6 % of total phenolics content. Kaempferol-3- O -rutinoside (0.001–0.968 μg/g), isorhamnetin-3- O -rutinoside (0.001–0.300 μg/g), taxifolin (0.006–0.078 μg/g), luteoloside (0.002–0.068 μg/g), prunin (0.043–33.333 μg/g), phlorizin (0.018–1.100 μg/g), and trans -piceid (0.013–0.472 μg/g) were also highly diverse. The fruit ripening period, breeding background and fruit type significantly influenced the PACs and phenolic glycosides. This study presents a complete profile of PACs and other major phenolics in 217 peach germplasms, and is expected to aid future peach breeding procedures targeted at producing plants rich in specific phenolics.